EFEKTIVITAS PROGRAM PELATIHAN KERJA UPTD BALAI LATIHAN KERJA DINAS TENAGA KERJA KOTA SEMARANG - Nina Widowati (Departemen Administrasi Publik, Universitas Diponegoro, 2021)
The job training program which organized by UPTD Balai Latihan Kerja Dinas Tenaga Kerja Kota Semarang to be less effective. This research is a qualitative descriptive study using a purposive technique. The results showed that: 1) The job training program organized by the UPTD Balai Latihan Kerja Dinas Tenaga Kerja Kota Semarang is good enough but it cannot be said to be effective because it has not met the requirements that are said to be effective, which is related to the achievement of goals or results, efficiency, and systems. maintenance. The unachieved target of the alumni absorption of training programs to work for companies or to establish independent businesses, curricula that are only basic or basic, and a short training time have resulted in aspects of achieving goals or results less effective. Limited facilities and infrastructure have resulted in job training programs not running optimally and with quality so that the efficiency aspect is less effective. The training program that cannot be guaranteed to take place every year and the condition of the training equipment which is not well maintained causes the maintenance system aspect to be less effective. 2) The target factor and the amount of assistance are inhibiting factors for the effectiveness of the UPTD Balai Latihan Kerja Dinas Tenaga Kerja Kota Semarang. The lack of discipline of the participants during the training process has an impact on their lack of competence so that target factors hinder the effectiveness of the program. The not optimal amount of operational budget provided by the central government and regional governments also has an impact on the low quality of training tools so that they are less relevant to industry needs, this makes the amount of assistance a factor in the effectiveness of the program.